Optimising Societal Welfare: The Strategic Role of Maqashid Shariah and Maslahah in Contemporary Islamic Economics and Business - Lestari, Rr. Hesti Setyodyah; Damayanti, Andia Kusuma; Masuwd, Mowafg Abrahem (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
The rapid growth of Islamic banking and financial institutions, both globally and in Indonesia, reflects the increasing relevance of Shariah-compliant economic systems. Institutions such as Islamic insurance, sukuk, pawnshops, mortgages, leasing, capital markets, mutual funds, and multi-level marketing have significantly evolved, driven by advancements in modern technology. These changes have transformed economic activities, including e-commerce transactions, digital payment systems, credit financing, international trade, and monetary control instruments. This paper critically examines the strategic role of Maqashid Shariah and Maslahah in shaping contemporary Islamic economics and business practices. By integrating classical Islamic jurisprudence with modern economic challenges, the study explores how Maqashid Shariah serves as a foundational framework for ethical and sustainable economic development. Furthermore, the analysis highlights the dynamic application of Maslahah in ensuring Shariah compliance while addressing the evolving needs of the global financial landscape. The findings underscore the potential of Islamic economic principles to promote inclusive growth, social justice, and long-term societal welfare